PENGALAMAN KELUARGA DALAM MERAWAT ANAK RETARDASI MENTAL DI SEKOLAH LUAR BIASA (SLB) - Putri Belia, Octavia Deva (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
Mental Retardation is a mental condition with the characteristic of Quetient Intellegencia level (IQ) below average and adaptive behavior disturbance. The most common mental retardation signs are ability of rolling over, sitting up, crawling, difficulty in speaking, and slow in mastering their daily activities. Families are often unable to accept the reality with their children condition that make them take no action and improper care. The aim of this study was to describe about some family experiences in caring their children with mental retardation. This study was conducted using a descriptive qualitative method, and this research was conducted at SLB C in Denpasar. There were four participants that selected by using purposive sampling and the data collection with in-depth interview, the interview was recorded and analyzed by using inductive data analysis and data processing using thematic analysis. As a result of this study found that the psychological response from families who have children with mental retardation is not easy. The parents said that the children have difficulties to perform their own activities, they have to provide assistance and training that can help the children have ability to perform their activities individually. Supports from others are needed. In effort to mentally retard child care family encounter obstacles such as barriers from psychological factors, children factors, financial factors, family factors, stigma, and vehicle factors. The parents hope there will be an individual ability of the children to perform their own activities and got a willingness to learn how to do their self activities individually.
Keywords: hildren with mental retardation; experience to care; family.